Investigation of the Effects of Saxagliptin in In Vitro and In Vivo Models of Diabetic Neuropathy - Oz, Samet; Orhan, Seval Ulku; Taslidere, Asli; Ozcan, Mete; Tekin, Suat (Wiley, 2025)
Diabetic neuropathy (DN), one of the most common microvascular complications of diabetes, is a condition involving complex pathophysiological mechanisms such as oxidative stress, inflammation, apoptosis, primarily resulting from chronic hyperglycemia. This study aimed to evaluate potential effects of Saxagliptin (Sax), a DPP-4 enzyme inhibitor, on in vitro and in vivo models of DN. Dorsal root ganglion neurons isolated from 1 to 2-day-old Wistar Albino rats were exposed to a high-glucose environment for 24 h to induce in vitro DN model. In this model, effects of Sax on cell viability and associated intracellular signaling pathways were investigated. In the in vivo model, streptozotocin-induced diabetic mice were divided into four groups: control, DN, DN+Sax-2, DN+Sax-10 (n = 10). For 15 days, DN group received 0.9% isotonic sodium chloride, while DN+Sax-2 and DN+Sax-10 groups were administered Sax orally via gavage at doses of 2 and 10 mg/kg, respectively, with concurrent nociceptive behavioral testing. At end of experiment, animals were decapitated, biochemical and histological analyses were performed on collected blood and pancreatic tissues. Sax, significantly increased cell viability via phosphoinositide 3-kinase pathway (p < 0.05). Compared to DN group, Sax-treated groups showed improvements in mechanical allodynia and thermal hyperalgesia; increased levels of superoxide dismutase, catalase, glutathione, total antioxidant status, interleukin-10; decreased levels of malondialdehyde, interleukin-1 beta, interleukin-6 (p < 0.05). Additionally, caspase-3 expression in pancreatic tissue was suppressed, and histopathological damage was markedly reduced (p < 0.0001). These findings suggest that Sax suppresses inflammation, inhibits oxidative damage and apoptosis, thereby reducing hyperalgesia, and may have therapeutic effects against DN.
Keywords: diabetes; DPP-4; DRG; neuropathic pain; Saxagliptin